A QuaternaryPoly(ethylene carbonate)-Lithium Bis(trifluoromethanesulfonyl)imide-Ionic Liquid-Silica Fiber Composite Polymer Electrolyte for Lithium Batteries. (1st September 2015) - Kimura, Kento; Matsumoto, Hidetoshi; Hassoun, Jusef; Panero, Stefania; Scrosati, Bruno; Tominaga, Yoichi
Highlights: A quaternary PEC-LiTFSI-Pyr14 TFSI-Silica fiber electrolyte was prepared by a solvent casting method. Both electrochemical and mechanical properties were improved by the presence of the Silica fiber. The electrolyte showed a t Li+ value of 0.36 with an anodic stability extended up to 4.5 V vs. Li/Li + . A prototype Li/LiFePO4 polymer cell delivered a discharge capacity of about 100 mAh g −1 (75 °C, C/15). Abstract: Poly(ethylene carbonate) (PEC) is known as an alternating copolymer derived from carbon dioxide (CO2 ) and an epoxide as monomers. Here, we describe a new quaternary PEC-based composite electrolyte containing lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) salt, N - n -butyl- N -methylpyrrolidinium bis(trifluoromethanesulfonyl) imide (Pyr14 TFSI) ionic liquid, and an electrospun silica (SiO2 ) fiber (SiF) with a submicron diameter in view of its possible applications in solid-state Li polymer batteries. A free-standing electrolyte membrane is prepared by a solvent casting method. The Pyr14 TFSI ionic liquid enhances the ionic conductivity of the electrolyte as a result of its plasticizing effect. The electrochemical properties, such as ionic conductivity and Li transference number ( t Li+ ), as well as mechanical strength of the electrolyte, are further improved by the SiF. We show that the quaternary electrolyte has a conductivity of the order of 10 −7 S cm −1 at ambient temperature and a high t Li+ value of 0.36 with an excellent flexibility. A prototype Li polymer cell using LiFePO4 as a cathode material is assembled and tested. We demonstrate that this battery delivers a reversible charge-discharge capacity close to 100 mAh g −1 at 75 °C and C/15 rate. We believe that this work may pave the road to utilize CO2 as a carbon source for highly-demanded, functional battery materials in future.